Prevalence and antibiotic resistance of Salmonella in organic and non-organic chickens on the Eastern Shore of Maryland, USA - Punchihewage-Don, Anuradha Jeewantha; Schwarz, Jurgen; Diria, Abdirahman; Bowers, John; Parveen, Salina (Frontiers in Microbiology, 2024)
Salmonella infections have been intensely increasing and becoming a universal public health crisis. This study investigated the prevalence of Salmonella in organic and non-organic chickens and the antimicrobial resistance profiles and virulence genes (invA, pagC, and spvC) in recovered Salmonella isolates. Whole chicken carcasses [organic (n=240) and non-organic (n=240)] were obtained monthly for one year (n=480) from a retail store on the Eastern Shore of Maryland. Salmonella isolation and identification were conducted by following the whole carcass enrichment method recommended by USDA-FSIS. Confirmed Salmonella isolates (organic n=76; non-organic n=137) were serotyped and tested for antibiotic susceptibility and virulence genes using standard methods. Forty-nine percent (237/480) of the carcasses were positive for Salmonella. Organic and non-organic positivity rates were 37.1% and 61.8%, respectively. A significantly higher Salmonella contamination was observed in non-organic chickens (p<0.05). The most common serovars were Salmonella Kentucky (47%), S. Infantis (35%), S. Enteritidis (6%), S. Typhimurium (5%), and S. Blockley (4%). Isolates were frequently resistant to at least one antibiotic (91.24%) or multidrug resistant (45.54%). Resistance was observed to tetracycline (82.8%), minocycline (42.3%), nitrofurantoin (40.3%), cefazolin (38.3%), ampicillin (32.1%), and ceftriaxone (26%). All isolates were susceptible to fluoroquinolone, carbapenem, and glycylcycline. The majority of isolates (99.1%) possessed at least one of three virulence genes of concern and 4.2% tested positive for all three. Ninety-five, 89, and 6.6% of isolates contained invA, pagC, and spvC genes, respectively. The spvC gene was not detected in serovars recovered from organic chickens though 92% and 82% of isolates were positive for invA and pagC. The frequency of Salmonella recovered from non-organic chickens possessing invA, pagC, and spvC genes were 97.1%, 89.8%, and 10.2%, respectively. Detection of invA and pagC genes showed no significant difference (p>0.05) between organic and non-organic chickens but a significantly higher spvC gene (p<0.05) was detected in non-organic chickens due to the majority of S. Enteritidis (92.3%) exclusively recovered from non-organic chicken carried spvC gene. This study reveals a high prevalence of Salmonella in both organic and non-organic chickens, which exhibit resistance to vital antibiotics and carry virulence genes, thereby creating a potential risk of salmonellosis.